Dynamics of biochemical markers of the connective tissue metabolism in the blood of rats after insertion of steel implants with diamond-like carbon coating into the femur (Bangladesh Journal of Medical Science, 2021)
Objective: It is known that the regeneration of bone tissue after implantation of any structuresdepends on the coating of their surface. Therefore, the research of the influence of steelimplants with diamond-like carbon coating on regeneration of bone tissue in the dynamics afterimplantation is a topical issue.Material and Methods: The study was conducted on 61 male rats,5 of them were intact animals. There were also 2 groups of rats with 28 animals in each group(the 1st group was the control one where implants were without diamond-like carbon coating,the 2nd group was experimental where the implants were without coating). We determined thecontent of glycoproteins, chondroitin sulfates, alkaline phosphatase, total calcium, oxyprolineand osteocalcin in the blood of rats on the 7th, 14th, 30th and 90th days after implantation.Resultsand Discussion: Group 2 rats had a faster osteointegration compared with the group 1 rats, whichwas manifested by the normalization of biochemical markers of bone metabolism (glycoproteins,chondroitinsulfats, oxyproline and osteocalcin) on the 90th day of an experiment.Conclusion:Using steel implants with diamond-like carbon coatings showed that the content of glycoproteinsand chondroitin sulfates increased only on the 7th day; oxyproline and osteocalcin increasedon the 7th, 14th and 30th days after implantation; on the 90th day the rates of these biochemicalmarkers reached the norm, indicating a high efficiency of osteointegration.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.81-85